(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: This research aims to evaluate the safety and efficiency of transrectal ultrasound the prostate biopsy at Thanh Hoa general hospital. Materials and Methods: A cross-sectional study. Results: From 1/11/2021 to 31/03/2024, in Urologic surgery department at Thanh Hoa general hospital, 72 patients entered the study. Average age: 70.6; Average PSA: 76.8 ng/ml, cancer prostate: 40.3 %. Complication rate: 16.7 %, the complications did not need surgery. Conclusions: The technical of transcrectal ultrasound guided the prostate biopsy via the rectum is a safe and efficient approach due to the low complication rate and the high success one.